Complications of Submucous Resection versus Septoplasty in Deviated Nasal Septum - Habibullah Khan, Habibullah Khan (Journal of Rawalpindi Medical College, 2020)
Introduction: A deviated or deflected septum is a condition in which the nasal septum consisting of bone and cartilage and that divide the nasal cavity into two halves is significantly off-center, or twisted, making breathing difficult. Two conventional methods that are septoplasty and sub-mucous resection were used for the correction of the deviated nasal septum with varying degrees of complications. Objective: The objective of this study was to compare the complications of sub-mucous resection and septoplasty in patients with the deviated nasal septum. Material and Methods: A Quasi-experimental study was conducted at the Department of Otolaryngology at Bolan Medical Complex, Quetta for a period of one year i.e. from 15-03-2015 to 20-09-2015. 100 patients were selected and divided into two groups. A total of 50 patients were selected for septoplasty and 50 for sub-mucous resection. Patients with nasal bone fracture and external nasal deformity were excluded from the study. Results: Postoperative complications like adhesions were found in 4 cases of each group. Septal perforation found in 3 patients of sub-mucous resection and one patient of septoplasty. Septal hematoma formed in 2 patients of sub-mucous resection only, supra-tip nasal deformity in 2 patients in both groups. Persistence of symptoms in 8 patients of septoplasty and one patient of sub-mucous resection while columellar restriction occurred in only one patent who underwent submucous resection. Conclusion: Sub-mucous resection procedure is technically relatively easy to perform with fewer complications than septoplasty so it deserves it prime role as a surgical procedure for nasal septum corrective surgery.